(untitled) (Research, Society and Development, 2022)
Social and economic transformations added to governmental measures registered in norms and decrees have stimulated discussions in the public sphere, aiming at greater efficiency in actions, improvements in the provision of educational services and fostering innovation. In this sense, university management becomes the focus of modernization and the search for greater user satisfaction with the provision of public services. On these issues, this work aims to analyze the directions of research aimed at university management, registered as scientific articles on the Web of Science platform, between the period from 1945 to 2020. Methodologically, it is a research with a quantitative approach, based on the from bibliometric analysis on the Web of Science platform, covering the period of consultation from 1945 to 2020. As a result, publication rates, specificities of more relevant research in the area of ​​university management, most cited authors and occurrences of words are recorded. It is concluded that, given the most relevant studies available on the Web of Science, there are no integrated approaches that involve issues such as efficiency, user satisfaction and innovation in higher education management, especially considering the Brazilian public sector.